Pemanfaatan tepung cangkang kijing taiwan untuk pertumbuhan kijing taiwan (Anodonta woodiana) - Runtu, Raymond Y.A.; Lumenta, Cyska; Sampekalo, Julius (Universitas Sam Ratulangi, 2016)
The purpuse of this research was to determine the effect of shell powder of Taiwanese mussel (Anodonta woodiana) at different doses on absolute growth, relative growth and survival rate of Taiwanese mussel. The treatment dosages of shell powder included A: 0 ppm, B: 10 ppm, C: 20 ppm, D: 30 ppm, and E: 40 ppm. Experimental design used was Complete Randomized Design with five treatments, each with three replications. The results showed that supplementation of 40 ppm of shell powder resulted in the best absolute growth and relative growth, namely 0.475 g and 1.84% respectively. Survival rate of Taiwanese mussel in all treatments during the experimental period was 100%. Keywords: Anodonta woodiana, Taiwanese mussel, shell powder, absolute growth, relative growth, survival rate